Structural characteristics, multifunctional applications, and research prospects of ferritin: a case study of sturgeon ferritin - Maqsood, Nida; Tang, Zuoliang; Ghafoor, Abu Zar; Li, Shuhong; Zhang, Zhiqing; Chen, Anjun; Zou, Zhiyong; Zhou, Man; Li, Meiliang (Frontiers in Nutrition, 2025)
Ferritin is a ubiquitous cage-shaped protein found in living organisms. Beyond its fundamental role in iron homeostasis, ferritin demonstrates growing application value in food engineering, nanocarrier systems, and biomedicine, owing to its unique self-assembly properties, exceptional stability, and biocompatibility. This review systematically summarizes the core structural features and physicochemical properties of ferritin, with a particular focus on its applications across three major domains. In food engineering, ferritin acts as both a carrier for bioactive compounds and a highly efficient, low-irritant iron fortificant, significantly enhancing nutrient stability, solubility, and bioavailability, thereby extending food shelf life. In the nanocarrier field, its nanocage structure provides an ideal platform for constructing nutrient and drug delivery systems, enabling targeted transport and controlled release. In biomedicine, ferritin is utilized in tumor imaging, targeted therapy, and inflammation biomarker detection. Using sturgeon liver ferritin as a specific example, this review details its unique advantages derived from its source, such as distinctive structure, enhanced stability, and application potential. Furthermore, the review identifies key challenges in ferritin research, including structural variability, digestive stability, and long-term safety concerns. It also outlines future research directions, highlighting the immense potential of ferritin in addressing critical challenges like fresh-cut food preservation. With advancing technology and multidisciplinary integration, ferritin is poised to become a powerful interdisciplinary tool.